Co-prescribing of SSRIs and TCAs in Australia: how often does it occur and who is doing it? - McManus, Peter (Blackwell Science Inc, 2001)
AIMS: To determine the frequency with which the selective serotonin re-uptake inhibitor (SSRI) antidepressants are used as add-on therapy to the tricyclic antidepressants (TCA) rather than as replacement therapy. METHODS: The data analysed were profiles of prescription records by date of supply to the patient. From within the national administrative dispensing claims database, the subset eligible for social security entitlements was identified as individuals by means of their coded permanent identification numbers (PINs). Following the initial supply of an SSRI in January 1996, the subsequent 6 months dispensing of SSRI and TCA antidepressants to these individuals was examined. The main outcome measure was the proportion of individuals to whom SSRIs and TCAs were dispensed concurrently, as an indirect measure of coprescription. In instances where a patient was receiving prescriptions for SSRIs and TCAs that had been written by the one doctor only, the major specialty of the doctor was investigated. RESULTS: 55 271 PINs were dispensed 63 865 SSRI prescriptions in January 1996 which represented over half (52%) of the total community SSRI prescriptions dispensed in that month. The number of these patients meeting the criteria for coprescription of SSRIs and TCAs over the next 6 months was 2773 (5%). The coprescribing instances were highest in Queensland and the prescribers most frequently involved had psychiatry major specialty codes. CONCLUSIONS: Among SSRI users there is a cohort of patients who, within the same time frame, are receiving supplies of a TCA, the nonselective drug that the SSRIs were designed to replace. This is indirect evidence of probable coprescription. Such combination use is of uncertain clinical and cost effectiveness, and carries additional risks. The SSRIs were included on the subsidy list in Australia on the basis of reasonable cost effectiveness as monotherapy compared with the TCAs. Our data imply that for some patients, antidepressant prescribing is inconsistent with the basis on which government subsidy was approved.